Adult Mouse Kidney Stem Cells Orchestrate the De Novo Assembly of a Nephron via Sirt2‐Modulated Canonical Wnt/β‐Catenin Signaling (Adv. Sci. 15/2022). Issue 15 (25th May 2022) - Han, Xiaobin; Sun, Zhongjie
Abstract : De Novo Generation of Kidney Organoids Using Adult Kidney Stem Cells Generation of kidney organoids using autologous kidney stem cells represents an attractive strategy for treating and potentially replacing the failing kidneys. In article number 2104034, Xiaobin Han and Zhongjie Sun report a previously unidentified adult kidney Sca1 + Oct4 + stem cells. Interestingly, culturing these stem cells led to de novo generation of self‐organizing nephrons and kidney‐like structures. This finding provides the first evidence that kidney stem cells are capable of de novo generating kidney organoids. This finding also offers a new opportunity for studying mammalian kidney development and personalized kidney regeneration.